2007
DOI: 10.1210/me.2005-0458
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of Mitochondrial Steroidogenic Acute Regulatory (StAR) Protein by Lon Protease: The Unexpected Effect of Proteasome Inhibitors

Abstract: Steroidogenic acute regulatory protein (StAR) is a vital mitochondrial protein promoting transfer of cholesterol into steroid making mitochondria in specialized cells of the adrenal cortex and gonads. Our previous work has demonstrated that StAR is rapidly degraded upon import into the mitochondrial matrix. To identify the protease(s) responsible for this rapid turnover, murine StAR was expressed in wild-type Escherichia coli or in mutant strains lacking one of the four ATP-dependent proteolytic systems, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 77 publications
6
105
1
1
Order By: Relevance
“…Eukaryotic Lon (37% identical to LonA of B. subtilis) (SI Appendix, Fig. S7) is involved in both the general degradation of misfolded proteins and in the specific remodeling of the mitochondrial proteins cytochrome C oxidase COX4-1, transcription factor A (TFAM), and the cholesterol regulator StAR (47)(48)(49)(50). It has been suggested that Lon could be a viable anticancer drug target as drugs that inhibit Lon activity lead to cancer cell apoptosis in vitro either due to uncontrolled accumulation of misfolded proteins in general or due to the failure to control a specific regulator (48,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic Lon (37% identical to LonA of B. subtilis) (SI Appendix, Fig. S7) is involved in both the general degradation of misfolded proteins and in the specific remodeling of the mitochondrial proteins cytochrome C oxidase COX4-1, transcription factor A (TFAM), and the cholesterol regulator StAR (47)(48)(49)(50). It has been suggested that Lon could be a viable anticancer drug target as drugs that inhibit Lon activity lead to cancer cell apoptosis in vitro either due to uncontrolled accumulation of misfolded proteins in general or due to the failure to control a specific regulator (48,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial proteins would similarly fail to be imported into the mitochondria. If mitochondrial proteins are not imported into the mitochondria properly, they are degraded rapidly by proteasomes (48). For example, preornithine transcarbamylase is degraded by proteasomes in the cytosol when its import is inhibited by oxidative stress (38).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-independent proteasomal degradation has been demonstrated for several mitochondrial proteins. For example, steroidogenic acute regulatory protein (StAR) is proteolysed independently of ubiquitin in the cytoplasm by proteasomes (48). Preornithine transcarbamylase is degraded in the cytoplasm by proteasomes when mitochondrial import is inhibited by Paraquat (38), but its ubiquitination was not detected despite extensive experimental efforts.…”
Section: Mppmentioning
confidence: 99%
“…Perhaps such substrates are more prone to misfolding or to damage in conditions of mitochondrial stress. In mammalian mitochondria, LON has been shown to degrade aconitase, an Fe/S protein, the steroidogenic acute regulatory protein (StAR), and the mitochondrial transcription factor A (TFAM) Granot et al 2007;Matsushima et al 2010). LON appears to play a role in cellular aging as in aged mice, the levels of functional LON decline, concomitant with an increase in oxidatively damaged mitochondrial proteins and increased mitochondrial dysfunction (Bota et al , 2005.…”
Section: Atp-dependent Proteolysis In the Mitochondrial Matrixmentioning
confidence: 99%